The Most Cited Article on Sustainable Development Goals: A bibliometric analysis - Fauzi, Syahrul; Purwoko; Winarsih; Maryono (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: This study investigates the main basis for public recognition of the merits of scientists, which has always been the system of scientific publications and citations. Purpose: The purpose of this study was to identify the most cited publications focusing on SDGs and identify the publications that contribute the most to the SDGs to provide readers with useful historical information on current relevant research. Methods: This study used bibliometric analysis in a qualitative descriptive approach. A search of all databases and journals accessible in Elsevier’s Scopus was performed on May 31st, 2024. The document search was performed using the query “SDGs,” yielding 17.834 results. The most cited papers were identified, and data were extracted. All references contained within the most cited articles were collected. Findings: The most cited articles were published in 97 different journals from 13 countries. The most cited article is “Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): An overview of viral structure and host response” by Astuti and Ysrafil, published in 2020 in the journal Diabetes and Metabolic Syndrome: Clinical Research and Reviews with 691 citations and on SDG 3: Good Health and Well-being. The largest contribution of SDG insightful articles was contributed by articles on SDG 3 (Good Health and Well-Being). Included are a list of the most cited articles, the top seven journals these publications most frequently appeared in, the top institutional affiliations, the top international collaborations of the most cited publications, the trend of subject area on SDGs, and publications by Cite Score Quartile. Conclusion: The most cited works regarding SDGs have been found and examined in this study. For further research, this study will be used as a historical reference. This study will also provide a guide to facilitate effective SDG research and offer insight into the developments of SDG research.